2003
DOI: 10.1063/1.1537246
|View full text |Cite
|
Sign up to set email alerts
|

Temperature induced changes on the structure and the dynamics of the “tetrahedral” glasses and melts of ZnCl2 and ZnBr2

Abstract: Glassy, supercooled, and molten ZnCl2 and ZnBr2 have been studied by Raman spectroscopy over the broad temperature range −196 to 800 °C in an effort to follow in detail the structural changes caused by temperature variation. A systematic study has also been undertaken for the corresponding crystalline polymorphs showing that each material exists in only one crystalline phase if water traces are not present. The reduced isotropic and anisotropic Raman spectra of the ZnCl2 and ZnBr2 glasses and melts are isomorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
61
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 87 publications
7
61
0
Order By: Relevance
“…On the basis of these results Lecocq et al 27 have not presented the experimental EM spectra, therefore it was not possible for us to consider the presence of other Zn x Cl 2 2xC2 anionic species, as for instance, the Zn 4 Cl 10 2 that was already observed for ZnCl 2 melts. 42 As discussed above, and supported by literature data, 33,34,38,41,42 we conclude that for X ZnCl 2 < 0.3, the main ionic species present in the ILs are the BMI C cation and the ZnCl 4 2 anion.…”
Section: The Raman Spectra Of Bmi/zncl 2 Ionic Mixturessupporting
confidence: 65%
See 2 more Smart Citations
“…On the basis of these results Lecocq et al 27 have not presented the experimental EM spectra, therefore it was not possible for us to consider the presence of other Zn x Cl 2 2xC2 anionic species, as for instance, the Zn 4 Cl 10 2 that was already observed for ZnCl 2 melts. 42 As discussed above, and supported by literature data, 33,34,38,41,42 we conclude that for X ZnCl 2 < 0.3, the main ionic species present in the ILs are the BMI C cation and the ZnCl 4 2 anion.…”
Section: The Raman Spectra Of Bmi/zncl 2 Ionic Mixturessupporting
confidence: 65%
“…Yannopoulos et al 42 have also observed a feature at 152 cm 1 for the ZnBr 2 melt that was assigned to a Zn 4 Br 10 2 species. These authors have predicted that the corresponding Zn 4 Cl 10 2 species would present a Raman feature at 265 cm 1 .…”
Section: The Raman Spectra Of Bmi/zncl 2 Ionic Mixturesmentioning
confidence: 93%
See 1 more Smart Citation
“…Manifestations of edge-sharing tetrahedra in Raman spectra are common in tetrahedral glasses, see for example ZnX 2 (X: Cl, Br) [27] and GeS 2 [28]. In both cases, the frequency of the ν 1 (A 1 ) vibrational mode associated with edge-sharing configurations is higher than that of the corresponding mode of apex-bridged species, which indicates species with stronger intratetrahedral bonding in the former.…”
mentioning
confidence: 99%
“…Raman spectroscopy is an inelastic light scattering technique that was previously used with success in studies on several molten salt systems [1][2][3][4][5][6][7] including MgCl 2 [7]. In the case of molten MgCl 2 , a clearly resolved band was observed at 205 cm -1 that was assigned to the symmetric stretch of the tetrahedral MgCl 4 2-species.…”
Section: Key Current Efficiency Issuesmentioning
confidence: 99%